Administering prevention or administering atrocities? Public affairs education in dark times. Issue 2 (July 2019) - Rubaii, Nadia; Appe, Susan; Lippez-De Castro, Sebastian
Despite repeated calls to temper the bureaucratic ethos and its associated process-oriented pathologies with more of a democratic ethos grounded in normative values and the public interest, the practice, research, and teaching of public administration continues to largely perpetuate the former. In this paper we build upon the work of Camila Stivers' book Governance in Dark Times and Nabatchi and colleagues' subsequent call to search for opportunities to better address issues of war, terrorism, climate change, economic calamity, refugee crises, and other atrocities which characterize dark times. We focus our attention on one specific issue within this realm, that of genocides and mass atrocities, as a way to illustrate that public servants—from street-level bureaucrats through high-level policy makers—may be part of the problem or part of the solution. We assert the responsibility of public affairs educators to ensure that their students are prepared to administer prevention or we risk that traditional administrative pathologies may lead them to inadvertently engage in administering atrocities. We position our overarching proposal in the context of fundamental public service values as well as the United Nations' Sustainable Development Goals (SDGs), particularly SDG 16. We also align our more specific recommendations with the Network of Schools of Public Policy, Affairs, and Administration's universal competencies and the core content domains of the Atlas for Public Management.